2014
DOI: 10.1039/c4em00108g
|View full text |Cite
|
Sign up to set email alerts
|

UV-visible absorbance spectroscopy as a proxy for peatland dissolved organic carbon (DOC) quantity and quality: considerations on wavelength and absorbance degradation

Abstract: Rachel; Jones, Timothy G.; Lebron, Inma. 2014. UV-visible absorbance spectroscopy as a proxy for peatland dissolved organic carbon (DOC) quantity and quality: considerations on wavelength and absorbance degradation. Environmental Science: Processes & Impacts, 16 (6

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
66
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(80 citation statements)
references
References 79 publications
10
66
1
3
Order By: Relevance
“…This agrees well with many earlier studies in which the link between COC (or absorbance of water) and TOC has been so intimate that it accurately predicts the concentration of TOC (Carter et al, 2012;Peacock et al, 2014). In our study, the a* of humic substances described color well, in agreement with earlier studies suggesting that humic substances comprise the majority of TOC in most freshwaters.…”
Section: The Toc-to-fe Ratio As An Estimate For Fe%supporting
confidence: 94%
“…This agrees well with many earlier studies in which the link between COC (or absorbance of water) and TOC has been so intimate that it accurately predicts the concentration of TOC (Carter et al, 2012;Peacock et al, 2014). In our study, the a* of humic substances described color well, in agreement with earlier studies suggesting that humic substances comprise the majority of TOC in most freshwaters.…”
Section: The Toc-to-fe Ratio As An Estimate For Fe%supporting
confidence: 94%
“…This is consistent with the results of Wickland et al (2007) who observed lower SUVA in DOC samples derived from fresh plant material compared to soil water extracts. Peacock et al (2014) suggest that E2:E3 and SUVA may be good indicators of between site differences in DOC quality; however, despite higher productivity at the restored site, there were no significant difference between soil water E2:E3 and SUVA between restored and unrestored peat fields (Table 2). This was likely due to dry conditions during the study period and limited hydrologic connectivity between residual peat layers and the newly deposited peat (McCarter and Price, 2015) that limited contact between soil pore water and the new litter.…”
Section: Discussioncontrasting
confidence: 54%
“…In contrast, Wallage et al (2006) observed an increase in E4:E6 following drain blocking. Peacock et al (2014) noted that E4:E6 ratios had greater temporal variation compared to E2:E3 and SUVA and suggest that this may make E4:E6 a good proxy for temporal change, but limit its utility for assessing treatment effects. GEP max was positively related to SUVA 254 indicating that more productive plots (large negative GEP) resulted in less aromatic DOC.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…DOC was measured as nonpurgeable organic carbon using an Analytical Sciences Thermalox Total Carbon analyser (Peacock et al, ). Samples were acidified (pH < 3), sparged with oxygen to remove inorganic carbon, and DOC concentrations calculated using a seven‐point calibration (0–60 mg L −1 ) curve with additional standards to check for drift, plus a quality control sample.…”
Section: Methodsmentioning
confidence: 99%